Preparation method of microbial immobilized filter material based on molecularly imprinted biochar

By conducting thermal solution modification and molecular imprinting of biochar materials, combined with fixed technology, to prepare high -efficiency and stable microbial fixed filter materials, solving the mechanical strength and adsorption selection of existing biological carbon filter when processing VOCs and adsorption options The problem of insufficient sexuality has achieved efficient removal and long -term stable operation.

CN119372197APending Publication Date: 2025-01-28INNER MONGOLIA BAOTOU STEEL GRP ENVIRONMENTAL ENG RES INST CO LTD +1

Patent Information

Application Number
CN202411941703.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing biochar filters have problems such as low mechanical strength, poor adsorption selectivity and insufficient treatment load when treating VOCs, resulting in low removal efficiency and short service life.

Method used

By optimizing the thermal solution and modification process of biological carbon materials, molecular seal modification and granification are carried out, combined with the fixed technology of polyvinyl/sodium alginate, forming a molecular printing biological carbon particles for fixed microorganisms, improving the mechanical strength of the filter material And adsorption selectivity.

Benefits of technology

The efficient removal rate of VOCS (can reach more than 98%), the improvement of mechanical strength, and the extension of the service life, and has the advantages of green environmental protection, low operation costs and stable performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a microbial immobilized filter material based on molecularly imprinted biochar. The preparation method comprises the following steps: (1) pyrolysis modification of biochar; (2) molecular imprinting modification and granulation; and (3) carrying out microbial immobilization on the biochar particles. According to the invention, waste straw chippings are used as raw materials, and the molecularly imprinted biochar particles with large specific surface area, rich pore structure, strong selective adsorption, high mechanical strength and excellent impact resistance are prepared through the processes of modification, pyrolysis, molecularly imprinted modification and granulation. Polyvinyl alcohol and sodium alginate are adopted as microbial immobilization materials, and the VOCs degrading bacteria loaded molecularly imprinted biochar particle filter material is formed through chemical crosslinking. The particle size of the filter material is 5-6 mm, the microorganism loading capacity reaches 3-4 mg / g, and the VOCs removal rate reaches 98% or above. The filter material can realize efficient treatment of VOCs, and has the advantages of environmental protection, stable removal effect, strong impact resistance, low operation cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biochar filter materials and relates to a method for preparing a microbial immobilized filter material based on molecular imprinted biochar. Background Art

[0002] In the treatment of industrial or domestic sewage, the release of various VOCs gases such as sulfides, nitrides, halogen derivatives, hydrocarbons and oxygen-containing organic matter not only causes the sewage treatment plant's unorganized waste gas emissions to exceed the standard, but may also have a serious impact on the quality of life of surrounding residents, causing odor troubles and health risks. Therefore, the development of efficient and stable VOCs removal technology has become a key demand in the field of sewage treatment and air pollution control.

[0003] The current mainstream deodorization and VOCs removal technologies include chemical oxidation, photocatalytic oxidation, liquid absorption and physical adsorption. However, although these physical and chemical processes are simple and require relatively little investment, they generally have disadvantages such as high operating costs, high reagent consumption, unstable treatment effects and incomplete VOCs removal. In contrast, biological deodorization technology uses domesticated microorganisms in solid-phase and solid-liquid phase reactors to degrade organic pollutants such as VOCs. It has the advantages of low energy consumption, low maintenance costs and low secondary pollution, and is an environmentally friendly treatment method.

[0004] At present, the filter media of biofilters are mainly made of ceramsite, bamboo charcoal, volcanic rock and other materials. Although they have a certain specific surface area and pore structure, they have problems such as long microbial biofilm period, low bioload and poor impact resistance, which leads to a long start-up period of biofilters and low VOCs removal efficiency, making it difficult to meet the needs of efficient deodorization. For example, the VOCs removal rate of bamboo charcoal filter media is about 75.7%, volcanic rock filter media is 73.3%, and ceramsite filter media is between 59.7% and 78.2%. When the amount of VOCs to be treated increases, the above-mentioned biofilter system is difficult to bear, resulting in a decrease in its treatment efficiency.

[0005] CN117339560A discloses a method for preparing filter material for treating VOCs based on sintered biochar, using waste straw debris as raw materials, and preparing sintered biochar with large specific surface area and high porosity through modification and sintering processes, and using polyvinyl alcohol and sodium alginate as curing agents to achieve microbial immobilization, forming a filter material that can efficiently remove VOCs. The biochar filter material exhibits good VOCs adsorption performance during application, but has the defects of low mechanical strength (compressive strength of 20~30kPa), and is easy to pulverize during use, affecting the service life; at the same time, the adsorption selectivity is not strong, and it is easy to be saturated by other gases during the adsorption process, affecting the removal effect of VOCs.

[0006] Molecular imprinting technology is a technology that enables materials to selectively recognize and adsorb specific molecules by introducing "imprinting sites" that match the shape and chemical properties of target molecules on the surface or pores of the material. This technology is widely used in the fields of environmental purification, sensors and separation. Molecular imprinting technology has the ability to specifically recognize target molecules, and "imprinting sites" can efficiently and selectively adsorb specific pollutants from complex mixtures. At the same time, molecular imprinting materials usually have strong chemical and thermal stability and can maintain their selectivity in acidic and alkaline environments, high temperatures or organic solvents. This makes molecular imprinting materials suitable for pollutant removal under a variety of harsh conditions. For example, CN115999517A discloses a method for molecular imprinting biochar to activate persulfate to target and degrade polycyclic aromatic hydrocarbons, CN117797867A discloses a molecular imprinting cerium oxide / biochar composite material and its preparation method and application, and CN118420039A discloses a method for molecular imprinting biochar to target and degrade polycyclic aromatic hydrocarbon naphthalene based on virtual templates. However, if molecularly imprinted biochar is simply used to treat VOCs, although it can improve the adsorption selectivity, it still has the defects of low mechanical strength and easy pulverization. For example, the compressive strength of molecularly imprinted biochar (20~30kPa) is insufficient, which will cause physical damage or pulverization in actual applications, resulting in reduced treatment efficiency and clogging of the filtration system; at the same time, molecularly imprinted biochar may cause rapid saturation of imprinting sites in complex gas mixtures due to competitive adsorption, thereby reducing the treatment efficiency.

[0007] Therefore, there is an urgent need to improve the existing biochar filter materials, enhance their mechanical strength and adsorption selectivity, and optimize the molecular imprinting process to enhance the overall performance of the filter materials to meet the performance requirements of efficient and stable treatment of VOCs. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a microbial immobilized filter material based on molecular imprinted biochar, by optimizing the pyrolysis modification process of the biochar material, so that the pyrolysis modified biochar material can complete molecular imprinting modification, and prepare it into biochar particles, and finally solidify the microorganisms to obtain a biofilter material with high mechanical strength, strong adsorption selectivity, high treatment load, and can treat VOCs without biofilm formation. The purpose of the present invention is achieved through the following specific technical solutions.

[0009] The primary aspect of the present invention is to provide a method for preparing an immobilized microbial filter material based on molecularly imprinted biochar, and the specific steps are as follows: (1) Pyrolysis modification of biochar: The mechanically crushed straw debris is washed and sieved, and the uniform debris is chemically modified to improve the subsequent pyrolysis performance; the modified debris is then placed in a microwave pyrolysis device for carbonization to form pyrolysis biochar powder; the biochar powder is subjected to secondary solvent modification to obtain modified biochar powder; (2) Molecular imprinting modification and granulation: The modified biochar powder prepared in step (1) is immersed in a molecular imprinting solution, stirred and mixed, and then an initiator is added and the reaction temperature is controlled to form imprinting sites containing template molecules. After elution and drying, molecularly imprinted biochar powder is obtained; the biochar powder is stirred and mixed with a small amount of straw debris and an adhesive, and molecularly imprinted biochar particles are formed by mechanical granulation; (3) Microbial immobilization of biochar particles: The molecularly imprinted biochar particles prepared in step (2) are mixed with activated sludge containing VOCs-degrading bacteria and allowed to stand to fully adsorb the microorganisms. The biochar particles saturated with microorganism adsorption are taken out and quickly immersed in a mixed solution of sodium alginate and polyvinyl alcohol to complete the slurry hanging to form a coating structure. The biochar particles are then taken out and added to a saturated boric acid solution containing CaCl2 and stirred to form a granular biochar filter material with immobilized microorganisms through chemical cross-linking.

[0010] Furthermore, the power of the microwave pyrolysis device described in step (1) is 500-700 W, the carbonization time is 20-30 min, the carbonization temperature is 200-700 ° C, and the temperature is gradually increased. The heating rate is controlled at 5-10 ° C / min, carbonization at 200-300 ° C for 1-2 h, carbonization at 300-500 ° C for 2-3 h, and carbonization at 500-700 ° C for 3-5 h, so as to improve the specific surface area, pore structure and adsorption capacity of the biochar.

[0011] Furthermore, the chemical modification described in step (1) is to soak the uniform debris in 30%~50% phosphoric acid solution for 10~15h and 5%~10% sodium bicarbonate solution for 15~20h, and then dry it at 80~100℃ for 12~24h to enhance the stability of subsequent pyrolysis and introduce phosphorus functional groups and alkaline functional groups (such as carboxylates and carbonates) to adjust the surface properties of biochar.

[0012] Unless otherwise specified in the present invention, ratios, percentages and concentrations are all based on mass.

[0013] Furthermore, the secondary solvent modification described in step (1) is to soak the biochar powder in a 5% to 10% sodium silicate solution for 4 to 6 hours and a 0.5% to 2% polyethyleneimine solution for 5 to 8 hours, so as to improve the hydrophobicity and VOCs adsorption capacity of the modified biochar.

[0014] Furthermore, the specific method of molecular imprinting modification of biochar in step (2) is: immersing the modified biochar powder in a molecular imprinting solution to form a non-covalent bond complex with the template molecule; then adding an initiator and controlling the temperature to start the polymerization reaction to form a molecular imprinting polymer with a specific recognition site; then removing the template molecule by elution, and obtaining the molecularly imprinted modified biochar powder after drying.

[0015] Preferably, the template molecule is a typical VOCs (benzene, toluene, xylene, etc.), dissolved in 50% to 80% (volume ratio to water) ethanol or methanol solvent; the functional monomer is 5% to 20% (the proportion of the functional monomer in the entire polymerization mixture) acrylic acid or methacrylic acid, and the cross-linking agent is 0.1% to 5% (the proportion of the cross-linking agent in the entire polymerization mixture) divinylbenzene or methylenebisacrylamide.

[0016] Preferably, the initiator is 0.5% to 1% azobisisobutyronitrile, the polymerization temperature is 60 to 80°C, and the reaction time is 4 to 8 hours; the eluent is a methanol-acetic acid solution, and the drying temperature is 50 to 70°C.

[0017] Furthermore, in step (2), the adhesive is one or more of 2%~5% sodium alginate solution, 5%~10% polyvinyl alcohol solution, 10%~15% starch solution, 2%~5% gelatin solution, 1%~3% carboxymethyl cellulose, and 5%~10% polylactic acid solution; and the ratio of the molecularly imprinted biochar powder to the straw scraps and the adhesive is 50%~70%:10%~30%:5%~25%.

[0018] Furthermore, in step (3), the functional microorganisms in the activated sludge containing VOCs-degrading bacteria are Pseudomonassp.strain Pseudomonas, Acinetobactersp. One or more of the Acinetobacter species have a relative abundance of more than 50%; the microbial load of the molecularly imprinted biochar particles is 3-4 mg / g; the ratio of the molecularly imprinted biochar particles to the activated sludge containing VOCs-degrading bacteria is 1:1-3:1; the concentration of sodium alginate in the mixed solution is 1%-3%, and the concentration of polyvinyl alcohol is 4%-6%; the ratio of the molecularly imprinted biochar particles, sodium alginate, and polyvinyl alcohol is 60%-70%: 10%-20%: 5%-10%, and the concentration of CaCl2 in the boric acid solution is 1%-2%; the ratio of the molecularly imprinted biochar particles to the saturated boric acid solution is 1:5-1:10.

[0019] Pseudomonassp.strain Pseudomonas, Acinetobactersp. Acinetobacter can be enriched from activated sludge in sewage treatment plants. The specific operation process is as follows: (1) Collection and storage of activated sludge: Collect activated sludge samples from aeration tanks or sedimentation tanks in sewage treatment plants and store them in sterile containers to avoid environmental pollution; active samples should be processed as soon as possible and placed in a 4°C refrigerator for short-term storage. The storage time is generally not more than 48 hours. (2) Pretreatment of activated sludge: Rinse the collected activated sludge samples with deionized water to remove attached impurities. Mix well under the action of a stirrer, let stand for 10 to 15 minutes, discard the supernatant, and retain the suspension rich in microorganisms. Use 200 to 500 μm and 50 to 200 μm filter cloths or fine meshes to filter in turn to remove residual particles and impurities. Repeat the above operation 3 to 4 times to obtain a relatively pure microbial suspension. (3) Enrichment culture of activated sludge: The pretreated activated sludge suspension was added to an inorganic salt solution (typical components of inorganic salts are: KH2PO4 0.5g / L, Na2HPO4 0.5g / L, MgSO4·7H2O 0.08g / L, FeSO4·7H2O 0.01g / L) at a ratio of 1:10, and a mixed solution of benzene, toluene, and xylene (total concentration of 50-100 mg / L, benzene: toluene: xylene molar ratio of 1:1:1) was added as the sole carbon source. The temperature of the sequencing batch reactor was controlled to be 30°C, pH to be 7-8, rotation speed to be 120-150 rpm, reaction time to be 6-8h, and drainage ratio to be 50%-70%, in order to enrich microorganisms that use VOCs as carbon sources. As the operation time increases (after the 10th to 15th day), the dosage of the mixed VOCs solution is gradually increased to increase the influent VOCs concentration in the reactor from 50 to 100 mg / L to 200 to 300 mg / L, 400 to 500 mg / L, and 800 to 1000 mg / L. At the same time, the inlet and outlet VOCs concentrations and sludge concentrations in the reactor are monitored until the microorganisms adapt to the high concentrations of VOCs and grow steadily. (4) Identification of microorganisms in activated sludge: After the enrichment culture is completed, the microbial DNA in the activated sludge is extracted, and the bacterial community structure is analyzed using 16S rRNA gene sequencing technology. The species and genus information of the microorganism is confirmed by comparison with known databases (such as NCBI or SILVA). When the target functional microorganism ( Pseudomonassp.strain Pseudomonas and / or Acinetobactersp. When the relative abundance of Acinetobacter exceeds 50%, the enrichment is considered successful.

[0020] Another aspect of the present invention is to provide a filter material obtained by the above preparation method.

[0021] Furthermore, the particle size of the filter material is between 5 and 6 mm, the microbial load reaches 3 to 4 mg / g, and the VOCs removal rate can reach more than 98%.

[0022] Another aspect of the present invention is to provide the use of the above filter material for removing VOCs.

[0023] Furthermore, the operating conditions for removing VOCs are as follows: adding the above filter material into a biofilter, the filling rate of the biofilter is 40-60%, the pH value in the biofilter is 7-9, the humidity is 40-60%, the temperature is 25-35°C, the filtration speed is 0.05-0.15 m / s, and the gas residence time is 10-30 s.

[0024] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing filter material for treating VOCs based on molecular imprinting biochar, using waste straw debris as raw materials, introducing phosphorus functional groups and alkaline functional groups (such as carboxylates and carbonates) through modification, pyrolysis and secondary modification processes; adjusting the surface properties of biochar powder, and improving the specific surface area, porosity, hydrophobicity and VOCs adsorption capacity of biochar powder. Through molecular imprinting modification and granulation, the VOCs adsorption selectivity of granular biochar is improved, and combined with the immobilization technology of polyvinyl alcohol / sodium alginate, molecular imprinting biochar particles of immobilized microorganisms are formed, providing the strength of biological filter material. The VOCs removal rate of the filter material can reach more than 98%, and the rapid adsorption-degradation of VOCs can be realized. It has the advantages of being green and environmentally friendly, no need for film formation, high mechanical strength, strong adsorption selectivity, strong impact resistance, stable pollutant removal effect, and low operating costs. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is described clearly and completely below. Obviously, the described implementation is only a part of the implementation of the present invention, not all of the implementation. Based on the implementation of the present invention, all other implementations obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.

[0026] A method for preparing a microbial immobilized filter material based on molecularly imprinted biochar comprises the following steps: (1) Pyrolysis modification of biochar: The mechanically crushed straw debris is washed and sieved, and the uniform debris is chemically modified to improve the subsequent pyrolysis performance; the modified debris is then placed in a microwave pyrolysis device for carbonization to form pyrolysis biochar powder; the biochar powder is subjected to secondary solvent modification to obtain modified biochar powder; (2) Molecular imprinting modification and granulation: The modified biochar powder prepared in step (1) is immersed in a molecular imprinting solution, stirred and mixed, and then an initiator is added and the reaction temperature is controlled to form imprinting sites containing template molecules. After elution and drying, molecularly imprinted biochar powder is obtained; the biochar powder is stirred and mixed with a small amount of straw debris and an adhesive, and then mechanically granulated to form molecularly imprinted biochar particles of 5 to 6 mm; (3) Immobilization of microorganisms on biochar particles: The molecularly imprinted biochar particles prepared in step (2) are mixed with activated sludge containing VOCs-degrading bacteria and allowed to stand for 4 to 6 hours to fully adsorb the microorganisms. The biochar particles saturated with adsorption of microorganisms are taken out and quickly immersed in a mixed solution of sodium alginate and polyvinyl alcohol to complete the slurry hanging to form a coating structure. The biochar particles are then taken out and added to a saturated boric acid solution containing CaCl2. After stirring for 10 to 15 hours, a granular biochar filter material with immobilized microorganisms is formed through chemical cross-linking.

[0027] The microwave pyrolysis device described in step (1) has a microwave power of 500-700W and a microwave treatment time of 20-30min. The carbonization temperature is 200-700°C, and the temperature is gradually increased with a heating rate of 5-10°C / min to ensure uniform heat distribution and control the release of pyrolysis gas; carbonization is performed at 200-300°C for 1-2h to remove moisture and easily volatile organic components; carbonization is performed at 300-500°C for 2-3h to completely decompose macromolecules (such as lignin and cellulose) in the biomass; carbonization is performed at 500-700°C for 3-5h to increase the carbon content, structural stability and specific surface area of ​​the biochar.

[0028] The chemical modification described in step (1) is to soak the uniform debris in 30%~50% phosphoric acid solution for 10~15h and 5%~10% sodium bicarbonate solution for 15~20h, and then dry it at 80~100℃ for 12~24h to enhance the stability of subsequent pyrolysis and introduce phosphorus functional groups and alkaline functional groups (such as carboxylates and carbonates) to adjust the surface properties of biochar.

[0029] In the present invention, the secondary solvent modification of the pyrolysis biochar in step (1) is performed by sequentially soaking in a 5% to 10% sodium silicate solution for 4 to 6 hours and a 0.5% to 2% polyethyleneimine solution for 5 to 8 hours to improve the hydrophobicity of the modified biochar and the adsorption capacity of VOCs.

[0030] The molecular imprinting modification of the biochar in step (2) is performed by immersing the modified biochar powder in a molecular imprinting solution at a ratio of 1:5 to 1:20 to form a non-covalent bond complex with the template molecule; then adding an initiator and controlling the temperature to start the polymerization reaction to form a molecular imprinting polymer with a specific recognition site; then removing the template molecule by elution, and obtaining the molecularly imprinted modified biochar powder after drying.

[0031] The template molecule described in step (2) is a typical VOCs (benzene, toluene, xylene, etc.), dissolved in 50% to 80% ethanol or methanol solvent; the functional monomer is 5% to 20% acrylic acid or methacrylic acid, and the crosslinking agent is 0.1% to 5% divinylbenzene or methylene bisacrylamide; The initiator in step (2) is 0.5% to 1% azobisisobutyronitrile, the polymerization temperature is 60 to 80°C, and the reaction time is 4 to 8 hours; the eluent is a 70%:30% methanol-acetic acid solution, and the drying temperature is 60°C; In step (2), the adhesive is one or more of 2% to 5% sodium alginate solution, 5% to 10% polyvinyl alcohol solution, 10% to 15% starch solution, 2% to 5% gelatin solution, 1% to 3% carboxymethyl cellulose, and 5% to 10% polylactic acid solution. For example, 3% sodium alginate + 7% polyvinyl alcohol is used in wet environments; or 12% starch + 4% gelatin is suitable for applications with high biodegradability requirements, or 2% carboxymethyl cellulose + 8% polylactic acid is suitable for applications with environmental protection and high strength requirements. The ratio of the molecular imprinted biochar to the straw scraps and the adhesive is 50% to 70% molecular imprinted biochar, 10% to 30% straw scraps, and 5% to 25% adhesive; the particle size of the granular biochar is 5-6 mm.

[0032] In step (3), the functional microorganisms in the activated sludge containing VOCs-degrading bacteria are Pseudomonassp.strain Pseudomonas, Acinetobactersp. One or more of the Acinetobacter species have a relative abundance of more than 50%; the microbial load of the granular biochar is 3-4 mg / g; the ratio of the molecularly imprinted biochar particles to the activated sludge containing VOCs-degrading bacteria is 1:1-3:1; the concentration of the sodium alginate solution is 1%-3%, and the concentration of the polyvinyl alcohol solution is 4%-6%; the ratio of the granular biochar, sodium alginate, and polyvinyl alcohol is 60%-70% molecularly imprinted biochar particles, 10%-20% sodium alginate, and 5%-10% polyvinyl alcohol; the concentration of the CaCl2 solution is 1%-2%, and the ratio of the molecularly imprinted biochar particles to the saturated boric acid solution is 1:5-1:10. Example 1

[0033] Microbial immobilized filter material based on molecularly imprinted biochar was prepared and its performance was tested.

[0034] (1) Pyrolysis modification of biochar: The mechanically crushed straw debris was cleaned and sieved, and the uniform debris was taken for chemical modification. The debris was soaked in 40% phosphoric acid solution for 12 hours, and then dried at 80°C for 12 hours to improve the pyrolysis performance; the dried debris was further soaked in 7% sodium bicarbonate solution for 18 hours, and then dried at 80°C for 12 hours. After the modification, the treated straw debris was placed in a microwave pyrolysis device and microwaved for 30 minutes at a microwave power of 700W. The temperature of the microwave pyrolysis device was gradually increased, and the heating rate was controlled at 5°C / min. Carbonization was carried out at 200-300°C for 2 hours to remove moisture and volatile organic components; carbonization was carried out at 350-450°C for 3 hours to completely decompose the macromolecules (such as lignin, cellulose, etc.) in the biomass; finally, carbonization was carried out at 600°C for 5 hours to increase the carbon content, structural stability and specific surface area of ​​the biochar. The carbonized biochar powder was then subjected to secondary chemical modification by being immersed in a 7% sodium silicate solution for 5 hours and then dried at 80°C for 12 hours; then immersed in a 1% polyethyleneimine solution for 6 hours and then dried for 12 hours to obtain secondary modified pyrolysis biochar powder.

[0035] (2) Molecular imprinting modification and granulation: The modified biochar powder obtained in step (1) is soaked in a 50% ethanol solvent at a ratio of 1:10, and after stirring and mixing, a functional monomer (10% acrylic acid) and a cross-linking agent (3% divinylbenzene) are added to form a non-covalent bond complex; then an initiator (1% azobisisobutyronitrile) is added, and the reaction temperature is controlled to 60°C and the reaction time is 8h to carry out a polymerization reaction to form a molecular imprinting polymer with benzene and toluene recognition sites; after multiple elutions (the eluent is a 70%:30% methanol-acetic acid solution), it is dried at 60°C for 2h to form a molecularly imprinted modified biochar powder; it is mixed with 20% straw chips and 20% adhesive (the adhesive can be a combination of 3% sodium alginate + 7% polyvinyl alcohol or 12% starch + 4% gelatin), and uniform stirring is ensured. The choice of adhesive can be based on the specific application scenario. For example, in a wet environment, 3% sodium alginate and 7% polyvinyl alcohol are preferred. In applications with high biodegradability requirements, a combination of 12% starch and 4% gelatin is preferred. The ratio of molecularly imprinted biochar powder to straw and adhesive is 60%:20%:20%. The mixture is then made into particles with a diameter of 5-6 mm by a mechanical granulation device.

[0036] (3) Immobilization of microorganisms on biochar particles: The molecularly imprinted biochar particles prepared in step (2) are mixed with activated sludge containing VOCs-degrading bacteria in a ratio of 2:1 and allowed to stand for 4 to 6 hours to allow the biochar particles to fully absorb the microorganisms in the sludge. Pseudomonassp. Pseudomonas and Acinetobactersp. One or more of Acinetobacter, the relative abundance of microorganisms in the activated sludge reaches more than 50%. After adsorption, the microbial load of the biochar particles is 3.5 mg / g. Take out the biochar particles that are saturated with adsorption of microorganisms, and quickly immerse them in a mixture of 2% sodium alginate solution and 5% polyvinyl alcohol solution for coating. The coated biochar particles are placed in a mixed solution of 1.5% CaCl2 solution and boric acid, the ratio of boric acid to CaCl2 is 7:1, and the ratio of biochar particles to saturated boric acid solution is 1:8. After 10 to 15 hours of stirring, it is fully cross-linked to form an immobilized microbial particle biochar filter material with high strength and adsorption performance.

[0037] A rapid adsorption test of typical VOCs (benzene and toluene) was conducted in a 1L biofilter based on molecularly imprinted biochar particles, and the filling rate of molecularly imprinted biochar particles was 50%. 1000 mg / L of benzene and toluene gas was continuously introduced, and the humidity of the biofilter was controlled to be 50%, pH to 8, temperature to 30℃, filtration speed to 0.1m / s, and gas residence time to 20s. The results showed that the VOCs concentration at the outlet was 350~400 mg / L, that is, the adsorption rate of VOCs by molecularly imprinted biochar particles was 60%~65%, and the adsorption amount was 25~30 mg / g.

[0038] The rapid adsorption test of typical VOCs (benzene and toluene) was carried out in a 1L biofilter using immobilized microbial filter material based on molecular imprinting biochar particles. The filling rate of the immobilized microbial filter material based on molecular imprinting biochar was 50%. 1000 mg / L of benzene and toluene gas was continuously introduced, and the humidity of the biofilter was controlled to be 50%, pH to 8, temperature to 30℃, filtration speed to 0.1m / s, and gas residence time to 20s. The results showed that the VOCs concentration at the outlet was 10~25mg / L, that is, the removal rate of VOCs by the immobilized microbial filter material based on molecular imprinting biochar was 97.5%~99%.

[0039] Comparative Example 1 Chemically modified sintered biochar microbial immobilization filter material was prepared and its performance was tested.

[0040] (1) Sintering modification of biochar: The mechanically crushed straw debris was cleaned and sieved, and the uniform debris was taken for chemical modification. The debris was soaked in 40% phosphoric acid solution for 12 hours, and then dried at 80°C for 12 hours to improve the sintering performance; the dried debris was further soaked in 7% sodium bicarbonate solution for 18 hours, and then dried at 80°C for 12 hours. After the modification was completed, the treated straw debris was placed in a muffle furnace for sintering. The sintering temperature was 500~600℃, and the sintering time was 8~9h. Then it was soaked in 1% polyethyleneimine solution for 6 hours, and then dried for 12 hours to obtain the sintered biochar powder after secondary modification.

[0041] (2) Sintering biochar granulation: Mix the modified biochar powder obtained in step (1) with 20% straw scraps and 20% adhesive (the adhesive can be a combination of 3% sodium alginate + 7% polyvinyl alcohol or 12% starch + 4% gelatin), and ensure uniform stirring. The choice of adhesive can be based on the specific application scenario. For example, in a wet environment, 3% sodium alginate and 7% polyvinyl alcohol are preferred. In applications with high biodegradability requirements, a combination of 12% starch and 4% gelatin is preferred. The ratio of biochar powder to straw and adhesive is 60%:20%:20%, and then the mixture is made into particles with a diameter of 5-6 mm by mechanical granulation equipment.

[0042] (3) Immobilization of microorganisms on biochar particles: The sintered biochar particles prepared in step (2) are mixed with activated sludge containing VOCs-degrading bacteria in a ratio of 2:1 and allowed to stand for 4 to 6 hours to allow the biochar particles to fully absorb the microorganisms in the sludge. Among them, the VOCs-degrading bacteria are Pseudomonassp. Pseudomonas and Acinetobactersp. One or more of Acinetobacter, the relative abundance of microorganisms in the activated sludge reaches more than 50%. After adsorption, the microbial load of the biochar particles is 3.5 mg / g. Take out the biochar particles that are saturated with adsorption of microorganisms, and quickly immerse them in a mixture of 2% sodium alginate solution and 5% polyvinyl alcohol solution for coating. The coated biochar particles are placed in a mixed solution of 1.5% CaCl2 solution and boric acid, the ratio of boric acid to CaCl2 is 7:1, and the ratio of biochar particles to saturated boric acid solution is 1:8. After 10 to 15 hours of stirring, they are fully cross-linked to form an immobilized microbial particle biochar filter material with good mechanical strength and adsorption performance.

[0043] The modified sintered biochar particles were used to conduct a rapid adsorption test of typical VOCs (benzene and toluene) in a 1L biofilter, and the filling rate of the sintered biochar particles was 50%. 1000 mg / L of benzene and toluene gas was continuously introduced, and the humidity of the biofilter was controlled to be 50%, pH to 8, temperature to 30℃, filtration speed to 0.1m / s, and gas residence time to 20s. The results showed that the VOCs concentration at the outlet was 600~700 mg / L, that is, the adsorption rate of sintered biochar particles for VOCs was 30%~40%, and the adsorption amount was 10~15 mg / g.

[0044] The rapid adsorption test of typical VOCs (benzene and toluene) was carried out in a 1L biofilter using an immobilized microbial filter material based on modified sintered biochar particles. The filling rate of the immobilized microbial filter material based on sintered biochar was 50%. 1000 mg / L of benzene and toluene gas was continuously introduced, and the humidity of the biofilter was controlled to be 50%, pH to 8, temperature to 30℃, filtration speed to 0.1m / s, and gas residence time to 20s. The results showed that the VOCs concentration at the outlet was 50~150 mg / L, that is, the removal rate of VOCs by the immobilized microbial filter material based on modified sintered biochar particles was 85%~95%.

[0045] Comparative Example 2 Pyrolysis biochar microbial immobilization filter material without molecular imprinting modification was prepared and its performance was tested.

[0046] (1) Pyrolysis modification of biochar: The mechanically crushed straw debris was cleaned and sieved, and the uniform debris was taken for chemical modification. The debris was soaked in 40% phosphoric acid solution for 12 hours, and then dried at 80°C for 12 hours to improve the pyrolysis performance; the dried debris was further soaked in 7% sodium bicarbonate solution for 18 hours, and then dried at 80°C for 12 hours. After the modification was completed, the treated straw debris was placed in a microwave pyrolysis device and microwaved for 30 minutes at a microwave power of 700W. The temperature of the microwave pyrolysis device was gradually increased, and the heating rate was controlled at 5°C / min. Carbonization was carried out at 200-300°C for 2 hours to remove moisture and volatile organic components; carbonization was carried out at 350-450°C for 3 hours to completely decompose the macromolecules (such as lignin, cellulose, etc.) in the biomass; finally, carbonization was carried out at 600°C for 5 hours to obtain pyrolysis biochar powder without secondary modification.

[0047] (2) Granulation of pyrolytic biochar: The modified pyrolytic biochar powder obtained in step (1) is mixed with 20% straw scraps and 20% adhesive (the adhesive can be a combination of 3% sodium alginate + 7% polyvinyl alcohol or 12% starch + 4% gelatin), and uniform stirring is ensured. The choice of adhesive can be based on the specific application scenario. For example, in a wet environment, 3% sodium alginate and 7% polyvinyl alcohol are preferred. In applications with high biodegradability requirements, a combination of 12% starch and 4% gelatin is preferred. The ratio of pyrolytic biochar powder to straw and adhesive is 60%:20%:20%. The mixture is then made into granules with a diameter of 5-6 mm by a mechanical granulation device.

[0048] (3) Immobilization of microorganisms on biochar particles: The pyrolysis biochar particles prepared in step (2) are mixed with activated sludge containing VOCs-degrading bacteria in a ratio of 2:1 and allowed to stand for 4 to 6 hours to allow the biochar particles to fully absorb the microorganisms in the sludge. Pseudomonassp. Pseudomonas and Acinetobactersp. One or more of Acinetobacter, the relative abundance of microorganisms in the activated sludge reaches more than 50%. After adsorption, the microbial load of the biochar particles is 3.5 mg / g. Take out the biochar particles that are saturated with adsorption of microorganisms, and quickly immerse them in a mixture of 2% sodium alginate solution and 5% polyvinyl alcohol solution for coating. The coated biochar particles are placed in a mixed solution of 1.5% CaCl2 solution and boric acid, the ratio of boric acid to CaCl2 is 7:1, and the ratio of biochar particles to saturated boric acid solution is 1:8. After 10 to 15 hours of stirring, it is fully cross-linked to form an immobilized microbial particle biochar filter material with high strength and adsorption performance.

[0049] The rapid adsorption test of typical VOCs (benzene and toluene) was carried out in a 1L biofilter using pyrolytic biochar particles without molecular imprinting modification, and the filling rate of molecular imprinting biochar particles was 50%. 1000 mg / L of benzene and toluene gas was continuously introduced, and the humidity of the biofilter was controlled to be 50%, pH to 8, temperature to 30℃, filtration speed to 0.1m / s, and gas residence time to 20s. The results showed that the VOCs concentration at the outlet was 500~600 mg / L, that is, the adsorption rate of VOCs by pyrolytic biochar particles without molecular imprinting modification was 40%~50%, and the adsorption amount was 15~20 mg / g.

[0050] The rapid adsorption test of typical VOCs (benzene and toluene) was carried out in a 1L biofilter using pyrolysis biochar immobilized microbial filter material without molecular imprinting modification. The filling rate of the pyrolysis biochar immobilized microbial filter material without molecular imprinting modification was 50%. 1000 mg / L of benzene and toluene gas was continuously introduced, and the humidity of the biofilter was controlled to be 50%, pH to 8, temperature to 30℃, filtration speed to 0.1m / s, and gas residence time to 20s. The results showed that the VOCs concentration at the outlet was 50~100 mg / L, that is, the removal rate of VOCs by the pyrolysis biochar immobilized microbial filter material without molecular imprinting modification was 90%~95%.

[0051] By comparing Example 1, Comparative Examples 1 and 2, it can be seen that the performance of the immobilized microbial filter material based on molecular imprinting biochar in Example 1 in VOCs treatment is significantly better than that of the other two comparative filter materials. The removal rate of Example 1 reaches 97.5%~99%, and the adsorption amount is 25~30 mg / g, which is significantly higher than the removal rate of 85%~95% and the adsorption amount of 10~15 mg / g of Comparative Example 1, and the removal rate of 90%~95% and the adsorption amount of 15~20 mg / g of Comparative Example 2, which indicates that the molecular imprinting modification technology significantly enhances the selective adsorption capacity of the filter material for target pollutants (benzene, toluene), and at the same time improves the adsorption capacity. In addition, Example 1 significantly improves the mechanical strength of the filter material through secondary modification and cross-linking immobilization technology, and can maintain stable performance in long-term operation and complex gas environments, while Comparative Example 1 has the risk of pulverization due to insufficient mechanical strength. Although the mechanical strength of Comparative Example 2 has been improved, it lacks molecular imprinting modification and is prone to performance degradation due to competitive adsorption. Therefore, Example 1 has the best comprehensive performance. The synergistic effect of molecular imprinting modification and microbial immobilization technology effectively improves the adsorption efficiency, removal rate and service life of the filter material. It is an efficient and environmentally friendly VOCs treatment technology. Although Comparative Examples 1 and 2 have improved the performance of traditional filter materials to a certain extent, they are still insufficient in adsorption selectivity and mechanical strength, and it is difficult to meet the actual application requirements of high efficiency and stability. Example 2

[0052] Microbial immobilized filter material based on molecularly imprinted biochar was prepared and its performance was tested.

[0053] (1) Pyrolysis modification of biochar: The mechanically crushed straw debris was cleaned and sieved, and the uniform debris was taken for chemical modification. The debris was soaked in 50% phosphoric acid solution for 10 hours, and then dried at 80℃ for 24 hours to improve the pyrolysis performance; the dried debris was further soaked in 5% sodium bicarbonate solution for 20 hours, and then dried at 80℃ for 24 hours. After the modification, the treated straw debris was placed in a microwave pyrolysis device and microwaved for 20 minutes at a microwave power of 700W. The temperature of the microwave pyrolysis device was gradually increased, and the heating rate was controlled at 10℃ / min. Carbonization was carried out at 200~300℃ for 1 hour to remove moisture and volatile organic components; carbonization was carried out at 300~400℃ for 2 hours to completely decompose the macromolecules (such as lignin, cellulose, etc.) in the biomass; finally, carbonization was carried out at 700℃ for 3 hours to increase the carbon content, structural stability and specific surface area of ​​the biochar. The carbonized biochar powder was then subjected to secondary chemical modification by being immersed in a 5% sodium silicate solution for 6 hours and then dried at 80°C for 12 hours; then immersed in a 2% polyethyleneimine solution for 5 hours and then dried for 12 hours to obtain secondary modified pyrolysis biochar powder.

[0054] (2) Molecular imprinting modification and granulation: The modified biochar powder obtained in step (1) was soaked in 80% methanol solvent at a ratio of 1:15, and after stirring and mixing, a functional monomer (5% methacrylic acid) and a crosslinker (0.1% methylene bisacrylamide) were added to form a non-covalent bond complex; then an initiator (0.5% azobisisobutyronitrile) was added, and the reaction temperature was controlled to 80°C and the reaction time was 4 hours to carry out a polymerization reaction to form a molecular imprinting polymer with a xylene recognition site; after multiple elutions (the eluent was a 60%:40% methanol-acetic acid solution), it was dried at 70°C for 2 hours to form a molecularly imprinted modified biochar powder; it was mixed with 30% straw chips and 15% adhesive (the adhesive was 5% sodium alginate + 10% polylactic acid) to ensure uniform stirring. The mixture was then made into granules with a diameter of 5 mm by a mechanical granulation device.

[0055] (3) Immobilization of microorganisms on biochar particles: The molecularly imprinted biochar particles prepared in step (2) were mixed with activated sludge containing VOCs-degrading bacteria in a ratio of 3:1 and allowed to stand for 6 hours to allow the biochar particles to fully absorb the microorganisms in the sludge. Pseudomonassp. Pseudomonas and Acinetobactersp. One or more of Acinetobacter, the relative abundance of microorganisms in the activated sludge reaches more than 50%. After adsorption, the microbial load of the biochar particles is 4 mg / g. Take out the biochar particles that are saturated with adsorption of microorganisms, and quickly immerse them in a mixture of 3% sodium alginate solution and 4% polyvinyl alcohol solution for coating. The coated biochar particles are placed in a mixed solution of 2% CaCl2 solution and boric acid, the ratio of boric acid to CaCl2 is 7:3, and the ratio of biochar particles to saturated boric acid solution is 1:5. After 15 hours of stirring, it is fully cross-linked to form an immobilized microbial particle biochar filter material with high strength and adsorption performance.

[0056] A rapid adsorption test of typical VOCs (xylene) was conducted in a 1L biofilter based on molecularly imprinted biochar particles, and the filling rate of molecularly imprinted biochar particles was 60%. 1000 mg / L xylene gas was continuously introduced, and the humidity of the biofilter was controlled to be 60%, pH to 7, temperature to 25℃, filtration speed to 0.05m / s, and gas residence time to 30s. The results showed that the VOCs concentration at the outlet was 150~200 mg / L, that is, the adsorption rate of VOCs by molecularly imprinted biochar particles was 80%~85%, and the adsorption amount was 30~35 mg / g.

[0057] The immobilized microbial filter material based on molecular imprinted biochar particles was used to conduct a rapid adsorption test of typical VOCs (xylene) in a 1L biofilter. The filling rate of the immobilized microbial filter material based on molecular imprinted biochar was 60%. 1000 mg / L xylene gas was continuously introduced, and the humidity of the biofilter was controlled to be 60%, pH to 7, temperature to 25℃, filtration speed to 0.05m / s, and gas residence time to 30s. The results showed that the VOCs concentration at the outlet was 5~20mg / L, that is, the removal rate of VOCs by the immobilized microbial filter material based on molecular imprinted biochar was 98%~99.5%. Example 3

[0058] Microbial immobilized filter material based on molecularly imprinted biochar was prepared and its performance was tested.

[0059] (1) Pyrolysis modification of biochar: The mechanically crushed straw debris was cleaned and sieved, and uniform debris was taken for chemical modification. The debris was soaked in 30% phosphoric acid solution for 15 hours, and then dried at 100°C for 12 hours to improve the pyrolysis performance; the dried debris was further soaked in 10% sodium bicarbonate solution for 15 hours, and then dried at 90°C for 18 hours. After the modification, the treated straw debris was placed in a microwave pyrolysis device and microwaved for 30 minutes at a microwave power of 500W. The temperature of the microwave pyrolysis device was gradually increased, and the heating rate was controlled at 5°C / min. Carbonization was performed at 200-300°C for 2 hours to remove moisture and volatile organic components; carbonization was performed at 300-500°C for 2 hours to completely decompose the macromolecules (such as lignin, cellulose, etc.) in the biomass; finally, carbonization was performed at 500°C for 4 hours to increase the carbon content, structural stability and specific surface area of ​​the biochar. The carbonized biochar powder was then subjected to secondary chemical modification by being immersed in a 10% sodium silicate solution for 4 hours and then dried at 100°C for 12 hours; then immersed in a 0.5% polyethyleneimine solution for 8 hours and then dried for 12 hours to obtain the secondary modified pyrolysis biochar powder.

[0060] (2) Molecular imprinting modification and granulation: The modified biochar powder obtained in step (1) was soaked in 60% ethanol solvent at a ratio of 1:12, and after stirring and mixing, a functional monomer (20% acrylic acid) and a crosslinker (5% divinylbenzene) were added to form a non-covalent bond complex; then an initiator (1% azobisisobutyronitrile) was added, and the reaction temperature was controlled to 70°C and the reaction time was 6 hours to carry out a polymerization reaction to form a molecular imprinting polymer with recognition sites for benzene, toluene and xylene; after multiple elutions (the eluent was a 50%:50% methanol-acetic acid solution), it was dried at 50°C for 4 hours to form a molecularly imprinted modified biochar powder; it was mixed with 10% straw chips and 25% adhesive (the adhesive was 2% sodium alginate + 5% polyvinyl alcohol + 10% starch solution) to ensure uniform stirring. The mixture was then made into granules with a diameter of 6 mm by mechanical granulation equipment.

[0061] (3) Immobilization of microorganisms on biochar particles: The molecularly imprinted biochar particles prepared in step (2) were mixed with activated sludge containing VOCs-degrading bacteria in a ratio of 1:1 and allowed to stand for 5 hours to allow the biochar particles to fully absorb the microorganisms in the sludge. Pseudomonassp. Pseudomonas and Acinetobactersp.One or more of Acinetobacter, the relative abundance of microorganisms in the activated sludge reaches more than 50%. After adsorption, the microbial load of the biochar particles is 3 mg / g. Take out the biochar particles that are saturated with adsorption of microorganisms, and quickly immerse them in a mixture of 1% sodium alginate solution and 6% polyvinyl alcohol solution for coating. The coated biochar particles are placed in a mixed solution of 1% CaCl2 solution and boric acid, the ratio of boric acid to CaCl2 is 1:1, and the ratio of biochar particles to saturated boric acid solution is 1:10. After 12 hours of stirring, it is fully cross-linked to form an immobilized microbial particle biochar filter material with high strength and adsorption performance.

[0062] A rapid adsorption test of typical VOCs (benzene, toluene, and xylene) was conducted in a 1L biofilter based on molecularly imprinted biochar particles, and the filling rate of molecularly imprinted biochar particles was 40%. A mixed gas of 1000 mg / L benzene, toluene, and xylene was continuously introduced, and the humidity of the biofilter was controlled to be 40%, pH to 9, temperature to 35℃, filtration speed to 0.15m / s, and gas residence time to 10s. The results showed that the VOCs concentration at the outlet was 200~250 mg / L, that is, the adsorption rate of VOCs by molecularly imprinted biochar particles was 75%~80%, and the adsorption amount was 25~30 mg / g.

[0063] The rapid adsorption test of typical VOCs (benzene, toluene, xylene) was carried out in a 1L biofilter using immobilized microbial filter material based on molecular imprinting biochar particles. The filling rate of the immobilized microbial filter material based on molecular imprinting biochar was 40%. A mixed gas of 1000 mg / L benzene, toluene and xylene was continuously introduced, and the humidity of the biofilter was controlled to be 40%, pH to 9, temperature to 35℃, filtration speed to 0.15m / s, and gas residence time to 10s. The results showed that the VOCs concentration at the outlet was 15~25mg / L, that is, the removal rate of VOCs by the immobilized microbial filter material based on molecular imprinting biochar was 97.5%~98.5%.

[0064] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention. The protection scope of the present invention is defined by the claims and their equivalent technical solutions.

Claims

1. A method for preparing a microbial immobilized filter material based on molecularly imprinted biochar, characterized in that: The following steps are involved: (1) Pyrolysis modification of biochar: The mechanically crushed straw debris is washed and sieved, and uniform debris is taken for chemical modification; the modified debris is then placed in a microwave pyrolysis device for carbonization to form pyrolysis biochar powder; the biochar powder is subjected to secondary solvent modification to obtain modified biochar powder; (2) Molecular imprinting modification and granulation: soaking the modified biochar powder prepared in step (1) in a molecular imprinting solution, stirring and mixing, adding an initiator and controlling the reaction temperature to form imprinting sites containing template molecules, and obtaining molecularly imprinted biochar powder after elution and drying; stirring and mixing the molecularly imprinted biochar powder with straw debris and an adhesive, and forming molecularly imprinted biochar particles by mechanical granulation; (3) Microbial immobilization of biochar particles: The molecularly imprinted biochar particles prepared in step (2) are mixed with activated sludge containing VOCs-degrading bacteria and allowed to stand to fully adsorb the microorganisms; the molecularly imprinted biochar particles saturated with microorganism adsorption are taken out and quickly immersed in a mixed solution of sodium alginate and polyvinyl alcohol to complete slurrying to form a coating structure; then the molecularly imprinted biochar particles are taken out and added to a saturated boric acid solution containing CaCl2, stirred, and a biochar particle filter material with microorganisms immobilized is formed through chemical cross-linking.

2. The preparation method according to claim 1, characterized in that: The power of the microwave pyrolysis device described in step (1) is 500-700 W, and the carbonization time is 20-30 min; the carbonization temperature is 200-700 ° C, and the temperature is gradually increased. The heating rate is controlled at 5-10 ° C / min, carbonization at 200-300 ° C for 1-2 h, carbonization at 300-500 ° C for 2-3 h, and carbonization at 500-700 ° C for 3-5 h.

3. The preparation method according to claim 1, characterized in that: The chemical modification described in step (1) is to soak the uniform crumbs in a 30% to 50% phosphoric acid solution for 10 to 15 hours, soak them in a 5% to 10% sodium bicarbonate solution for 15 to 20 hours, and then dry them at 80 to 100°C for 12 to 24 hours.

4. The preparation method according to claim 1, characterized in that: The biochar powder was soaked in 5%~10% sodium silicate solution for 4~6 hours and in 0.5%~2% polyethyleneimine solution for 5~8 hours.

5. The preparation method according to claim 1, characterized in that: The specific method of molecular imprinting modification of biochar in step (2) is: immersing the modified biochar powder in a molecular imprinting solution to form a non-covalent bond complex with the template molecule; then adding an initiator and controlling the temperature to start the polymerization reaction to form a molecular imprinting polymer with a specific recognition site; then removing the template molecule by elution, and obtaining the molecularly imprinted modified biochar powder after drying.

6. The preparation method according to claim 5, characterized in that: The template molecule is one or more of benzene, toluene and xylene, and the template molecule is dissolved in 50% to 80% ethanol or methanol solvent; the functional monomer is 5% to 20% acrylic acid or methacrylic acid, and the crosslinking agent is 0.1% to 5% divinylbenzene or methylene bisacrylamide.

7. The preparation method according to claim 5, characterized in that: The initiator is 0.5% to 1% azobisisobutyronitrile, the polymerization reaction temperature is 60 to 80° C., and the reaction time is 4 to 8 hours; the eluent is a methanol-acetic acid solution, and the drying temperature is 50 to 70° C.

8. The preparation method according to claim 1, characterized in that: In step (2), the adhesive is one or more of 2% to 5% sodium alginate solution, 5% to 10% polyvinyl alcohol solution, 10% to 15% starch solution, 2% to 5% gelatin solution, 1% to 3% carboxymethyl cellulose, and 5% to 10% polylactic acid solution; the ratio of the molecularly imprinted biochar powder to the straw scraps and the adhesive is 50% to 70%: 10% to 30%: 5% to 25%.

9. The preparation method according to claim 1, characterized in that: In step (3), the functional microorganisms in the activated sludge containing VOCs-degrading bacteria are Pseudomonassp. strain Pseudomonas, Acinetobacter sp. One or more of the Acinetobacter species have a relative abundance of more than 50%; the microbial load of the molecularly imprinted biochar particles is 3-4 mg / g; the ratio of the molecularly imprinted biochar particles to the activated sludge containing VOCs-degrading bacteria is 1:1-3:1; the concentration of sodium alginate in the mixed solution is 1%-3%, and the concentration of polyvinyl alcohol is 4%-6%; the ratio of the molecularly imprinted biochar particles, sodium alginate, and polyvinyl alcohol is 60%-70%: 10%-20%: 5%-10%, and the concentration of CaCl2 in the boric acid solution is 1%-2%; the ratio of the molecularly imprinted biochar particles to the saturated boric acid solution is 1:5-1:

10.

10. The filter material obtained by the preparation method according to any one of claims 1 to 9 is used to remove VOCs, characterized in that: The particle size of the filter material is between 5 and 6 mm, and the microbial load is 3 to 4 mg / g. The operating conditions for removing VOCs with the filter material are as follows: the filter material is added to the biofilter, the filling rate of the biofilter is 40 to 60%, the pH value in the biofilter is 7 to 9, the humidity is 40 to 60%, the temperature is 25 to 35°C, the filtration speed is 0.05 to 0.15 m / s, and the gas residence time is 10 to 30 s.

Citation Information

Patent Citations

  • Method for targeted degradation of polycyclic aromatic hydrocarbon by activating persulfate with molecularly imprinted biochar

    CN115999517A

  • Preparation method of filter material for treating VOCs (Volatile Organic Compounds) based on sintered charcoal

    CN117339560A

  • Molecularly imprinted cerium oxide / biochar composite material as well as preparation method and application thereof

    CN117797867A

  • Virtual template-based method for targeted degradation of polycyclic aromatic hydrocarbon naphthalene by molecularly imprinted biochar

    CN118420039A

  • Nano photocatalyst of possessing function of molecular engram, preparation method and usage

    CN1915487A

Cited By

  • High-nutrition vegetable cultivation seedling substrate and preparation method thereof

    CN121014473A